1998
DOI: 10.3109/10253899809167288
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Hippocampal Cell Numbers in Young and Aged Rats Submitted to Chronic Unpredictable Stress. Comparison with the Effects of Corticosterone Treatment

Abstract: Exposure of rats to sustained stress has been associated with behavioural impairments, the degree of impairment being greater with increasing age of the subject. Although the behavioural deficits have been frequently attributed to stress-induced neuronal loss in the hippocampus, the validity of that view may be disputed since it is based on data collected using conventional morphometric methods which are subject to bias. The question of whether stress per se does indeed induce hippocampal cell losses was there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
51
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(66 citation statements)
references
References 54 publications
12
51
1
Order By: Relevance
“…Finally, and as expected (Andrade et al 2002;Cardoso et al 2013), the old-onset caloric restriction treatment did not induce neuronal loss in the aged animals. In fact, regarding the total number of neurons, the present study corroborates previous works (Rapp and Gallagher 1996;Sousa et al 1998) demonstrating that aging did not induce neuronal loss in the hilus of the dentate gyrus. Interestingly, we have found that oldonset caloric restriction treatment during 6 months did not induce neuronal death in the dentate hilus.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, and as expected (Andrade et al 2002;Cardoso et al 2013), the old-onset caloric restriction treatment did not induce neuronal loss in the aged animals. In fact, regarding the total number of neurons, the present study corroborates previous works (Rapp and Gallagher 1996;Sousa et al 1998) demonstrating that aging did not induce neuronal loss in the hilus of the dentate gyrus. Interestingly, we have found that oldonset caloric restriction treatment during 6 months did not induce neuronal death in the dentate hilus.…”
Section: Discussionsupporting
confidence: 92%
“…Although it can be argued that deficits in the hippocampus-to-PFC projections may be solely the conse- quence of damage to the projecting areas, there are several reasons why this is an unlikely explanation for the present results. First, although chronic stress can impose structural damage to particular hippocampal subfields (Sousa et al, 2000;McEwen, 2001), it does not affect the volume and number of neurons in the subiculum (present study) and CA1 (Sousa et al, 1998). Second, identical stimulation intensities produced similar baseline PSPs (waveform and amplitude) in stressed and control animals, which indicates the intactness of both the projecting area and connecting pathway.…”
Section: Discussionmentioning
confidence: 66%
“…Briefly, animals were exposed once daily to a stressor (1 h/d) of one of several aversive stimuli [cold water (18°C), vibration, restraint, overcrowding, exposure to a hot air stream]; the stressors were presented in random order for the duration of the experiment. This stress paradigm was shown previously to result in persistently elevated plasma levels of corticosterone, the primary glucocorticoid of the rat (for details, see Sousa et al, 1998). Another group of 10 rats were handled daily and served as controls (CONs).…”
Section: Animals and Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the behavioral level, exposure to stress has been reported to increase anxiety-related behavior and to impair learning and memory [3,4]. Many animal studies have demonstrated that chronic stress, as well as chronic corticosterone treatment, results in learning and memory deficits on several behavioral tasks, including the water-maze and passive-avoidance tests, and this impairment was accompanied by hippocampal damage [5][6][7][8][9][10]. In addition, Ader and Cohen et al and McEwen and Stellar et al reported that repeated stress is a risk factor for psychosomatic psychiatric illness, such as anxiety [11,12].…”
Section: Introductionmentioning
confidence: 99%